DEVELOPMENT OF STATIC ARMOUR - Cahyono Ikhsan (Jurnal Riset Rekayasa Sipil, 2018)
Armour layer is the type of gravel bed composed on the bed surface with pores between the composing grains as the place of sand to stay and lock the pores. This research was carried out in the Hydraulic Laboratory by using the main infrastructure of sediment flume from Plexiglas in 0.60 m width, 10.00 m length, and 0.45 m height dimension. The base gradients used was parallel to the water surface gradients, which were 1%, 1.4%, 1.8%, 2.2%, and 2.6%. The constant flow debit was at 25 l/s, 30 l/s, 40 l/s and 45 l/s capacity. The materials consisted of sand and gravel and were evenly mixed in 5 different grain size variations. At each running, there were 2 phases of occurrence: eroded surface and equilibrium. The instruments used during the running were digital current meter, point gauge, and sediment traps.The results of this research indicated armour layer formula stated in un-dimensional number with an average bedload limit of 0.8 mm to 2.9 mm, uniformity coefficient of 2.5 to 5, and critical shear stress of 0.61 N/m2 to 2.7 N/m2. and with minimum base shear stress of 6 N/m2.